(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
Nepal’s decentralized forest governance has now included a new actor, i.e. REDD+ which is a mechanism based on market for mitigation of climate change through conservation of forest. This paper aims to shed lights on the REDD+ effect on community forestry governance, and local livelihood. For this various published articles and reports were reviewed and analyzed. Organizations like ICIMOD, FECOFUN and ANSAB are leading a pilot project in community forestry on measurement of carbon and equalizing benefit. The major objective of the REDD+ program is to reduce forest carbon emissions by providing financial incentives for developing countries. The impacts of the implication of the REDD+ is more questionable preceding its 10th anniversary. Special income generating activities and awareness programs have been implemented by the REDD+ pilot project targeting the poor, women, disadvantaged groups and indigenous people. While some study findings show the REDD+ gave priority to the carbon outcome rather than community forestry’s forest management objective which threatens the objective of meeting the local needs of people. Analysis also showed that REDD+ policies have been developed and interventions are made in a way local people’s participation and representation of their voices is limited which may weaken and reverse the trend of forest decentralization. The involvement of the new actors in forest politics can be seen as a proof of positive impact of implementation of REDD+.